Facial Reanimation after Acoustic Neuroma Resection: Options and Timing of Intervention - Boahene, Kofi (Facial Plastic Surgery, 2015)
Facial paralysis following acoustic neuroma (AN) resection can be devastating, but timely and strategic intervention can minimize the resulting facial morbidity. A central strategy in reanimating the paralyzed face after AN resection is to restore function of the native facial muscles using available facial nerves or repurposed cranial nerves, mainly the hypoglossal or masseter nerves. The timing of reinnervation is the single most influential factor that determines outcomes in facial reanimation surgery. The rate of recovery of facial function in the first 6 months following AN resection may be used to predict ultimate facial function. Patients who show no signs of recovery in the first 6 months, even when their facial nerves are intact, recover poorly and are candidates for early facial reinnervation. With delay, facial muscles become irreversibly paralyzed. Reanimation in irreversible paralysis requires the transfer of functional muscle units such as the gracilis or the temporalis muscle tendon unit.
Keywords: facial paralysis; acoustic neuroma; vestibular schwannoma; reversible paralysis